Reducing Psychotropic Use in Older Non-demented Spanish Care Home Residents: a Before-After Comparison of Three Methods - Petersen, Curtis L.; Curto, David; Mishra, Manish K.; Cano, Pedro; Weeks, Bill (Journal of General Internal Medicine, 2019)
Recognizing that Spain has the highest rate of antipsychotic prescribing in Western Europe,1 the Spanish Geriatrics and Gerontology Society has encouraged reducing psychotropic medication use in long-term settings.2 In a quality improvement effort designed to do that, we found that administration of any of 3 interventions—application of STOPP/START criteria, medication-focused team rounds (TR), or a decision aid (DA)—effectively reduced psychotropic use among older Spanish nursing home residents with dementia, though STOPP/START criteria application was most effective.3 While care home residents with dementia are at risk for psychotropic overuse and their sequelae, so might be those without dementia.4 Therefore, we sought to analyze patients without dementia who obtained any of the 3 interventions we studied in Sanitas Mayores (Spain), a Bupa-affiliated aged care network.